2021
DOI: 10.1038/s41598-021-98200-8
|View full text |Cite
|
Sign up to set email alerts
|

Outcome, demography and resource utilization in ICU Patients with delirium and malignancy

Abstract: Delirium in the general intensive care unit (ICU) population is common, associated with adverse outcomes and well studied. However, knowledge on delirium in the increasing number of ICU patients with malignancy is scarce. The aim was to assess the frequency of delirium and its impact on resource utilizations and outcomes in ICU patients with malignancy. This retrospective, single-center longitudinal cohort study included all patients with malignancy admitted to ICUs of a University Hospital during one year. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…This frequency is similar to previous reports on critically ill, but not terminally ill, patients with cancer requiring ICU care, which ranges from 22.9% to 39.3%. 22-24 It is also comparable with rates of delirium in ICU patients without cancer, which range from 20% to 80%. 9,28 In addition, we also found that patients with delirium had significantly higher ICU and hospital mortality compared with patients without delirium.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…This frequency is similar to previous reports on critically ill, but not terminally ill, patients with cancer requiring ICU care, which ranges from 22.9% to 39.3%. 22-24 It is also comparable with rates of delirium in ICU patients without cancer, which range from 20% to 80%. 9,28 In addition, we also found that patients with delirium had significantly higher ICU and hospital mortality compared with patients without delirium.…”
Section: Discussionmentioning
confidence: 74%
“…8,10,29,30 However, this association is yet to be fully appreciated in patients with cancer admitted to the ICU. Sieber et al 24 found delirium in this patient subgroup to increase hospital mortality by almost 6-fold in univariable analysis, but results failed to maintain significance after controlling for severity of illness, sepsis, and shock. On the other hand, Sanchez-Hurtado et al 22 noted a lower ICU mortality in patients with cancer diagnosed with delirium (12%) than in those with no delirium (15%).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The total score of patient's readiness for separation is 26. When the patient obtains a score of above 17, he/she is ready to be separated from mechanical ventilation 27,28 . Burn et al (1990) believed that, this checklist is able to predict the successful separation of patient from mechanical ventilation by 85% for 72 hours 24,26 .…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the patients may be exposed to hypoactive delirium and be neglected by the treatment staff due to their calm appearance and, therefore, be susceptible to pressure ulcers or pneumonia more frequently. This group of patients, moreover, has symptoms of lethargy, impatience, and depression (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%